Low proportion of contact among people attending early detection for pulmonary tuberculosis in South Denpasar I Public Health Centre year 2012 - Anak Agung Gede Agung; Anak Agung Sagung Sawitri; Dewa Nyoman Wirawan (Public Health and Preventive Medicine Archive, 2013)
Family members with positive BTA tuberculosis (TB) are vulnerable to be infected due to regular contact. However, awareness of early detection is still low, resulting in low rates of TB suspect identification and low detection of new cases in the public health centre. The study aims to measure the proportion of contacts in the house for people attending early detection for pulmonary tuberculosis, and to analyse the influence of perception of contacts to the behavior of early detection. This cross-sectional analytic study include 110 respondents taken from all family members of BTA pulmonary TB cases as recorded in TB register at South Denpasar I Public Health Center between 2010 and 2011. There were 49 samples who have ever underwent early detection and 61 samples have not. Data collected were analysed using univariate, bivariate (chi square) and multivariate with cox regression. The proportion of contact in the house who underwent early detection is still low (22.55%). The perception of vulnerability and threat were found to be associated with the early detection behavior. Cox regression analysis however showed none of those variables associated with the early detection of pulmonary tuberculosis. The study concluded that only small proportion of people who had contact with TB patient in a house was underwent early detection. The perception of vulnerability and threat influence the early detection behavior of pulmonary tuberculosis in South Denpasar I Public Health Center. The awareness campaign to increase early detection of pulmonary tuberculosis needs to be improved through enhancing the knowledge regarding the spread of TB and its symptoms.